Przyczyny, płaszczyzny i przebieg konfliktów w małżeństwach bezdzietnych - Przybył, Iwona (Wydawnictwo Naukowe UAM, 2002)
This paper shows results of the author’s study carried out in the Wielkopolska region in 1999 among 140 childless married couples. The author presents the results of the analysis of the communication patterns among childless spouses and the course of marital quarrels. It was established that these couples are rather high-quality relationships in that respect. The main reasons of marital quarrels are: the disbursements, division of spouse’s duties and the form of spending the leisure time. It was established that infertile wives and husbands are not outspokenness in marital communication. The quarrels between partners who don’t cooperate with each other have the disintegrational character.
Causes, planes and the course of conflicts in childless families